Prenatal diagnosis of the recurrent 1q21.1 microdeletions in fetuses with ultrasound anomalies and review of the literature - Liu, Lei; Lei, Tingying; Guo, Fei; Ma, Chunling; Zhen, Li; Zhang, Lina; Li, Dongzhi (Frontiers in Genetics, 2024)
Objective: The recurrent 1q21.1 microdeletion syndrome is an autosomal dominant disorder and characterized by dysmorphic facial features, microcephaly, developmental delay, and congenital defects. However, most studies on the distal deletions in the 1q21.1 region were diagnosed postnatally. This study was aimed to provide a better understanding of the ultrasound and molecular findings of fetuses with the recurrent 1q21.1 microdeletions in prenatal diagnosis. Methods: In this retrospective study, we reported 21 cases with the recurrent 1q21.1 microdeletion syndrome diagnosed at our prenatal diagnostic center from January 2016 to January 2023. The clinical data were reviewed for these cases, including the maternal demographics, indications for invasive testing, ultrasound findings, CMA results and pregnancy outcomes. Results: In the study, a total of 21 cases with the recurrent 1q21.1 microdeletions were diagnosed prenatally by CMA. Fifteen cases were described with ultrasound indications and the most common findings were: increased nuchal translucency (NT) (26.7%), intrauterine growth retardation (IUGR) (26.7%), congenital heart defects (CHD) (20%), and congenital anomalies of the kidney and urinary tract (CAKUT) (13.3%). All the cases with the distal 1q21.1 deletions contain the common minimal region (located between BP3 and BP4) and 8 OMIM genes. Parental studies to determine inheritance of the deletion were performed for 8 cases and half of them were inherited from one of the parents. Pregnancy outcomes were available for 9 cases; 8 (88.9%) pregnancies were determined to be terminated and 1 (11.1%) was full term delivery. Conclusions: To our knowledge, this is the largest study to found that fetuses with the recurrent 1q21.1 microdeletions were closely associated the increased NT, CHD, IUGR and CAKUT. In addition, we are the first to report that cerebral ventriculomegaly might be associated with the recurrent 1q21.1 microdeletions. More comprehensive studies are needed for a better understanding of the prenatal phenotype–genotype relationship of the recurrent 1q21.1 microdeletion syndrome in the future